(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Genetic variability, heritability and selection response were studied among rice genotypes for yield attributing traits. Nine rice genotypes were evaluated in randomized complete block design with two replications at the University of Agriculture Peshawar-Pakistan during 2018. Significant differences were observed among the rice genotypes for all the traits. Pakhal took maximum value for Culm length (113.6 cm), Panicle length (29.05 cm), Secondary branches panicle-1 (31.4), Grain length (10 mm), Spikelets panicle-1 (162.8) and Grains panicle-1 (122.7 g). However genotype NIAB-IR-8 took maximum value for 100 grain weight (2.9 g) and Grain yield plant-1 (30.28 g). High heritability and genetic advance were observed for all the studied traits viz. Culm length (0.95 and 27.77), Panicle length (0.84 and 3.83), Grain length (0.62 and 0.78), Secondary branches panicle-1 (0.66 and 6.19), Spikelets panicle-1 (0.59 and 21.82), Grains panicle-1 (0.75 and 15.82), 100 grain weight (0.76 and 0.31) and Grain yield plant-1 (0.95 and 13.34). On the basis of superiority for yield attributing traits Pakhal and NIAB-IR-8 could be recommended for future use in rice breeding programs. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 55-60